2013
DOI: 10.1021/ac401471n
|View full text |Cite
|
Sign up to set email alerts
|

Paper-Based Solid-Phase Multiplexed Nucleic Acid Hybridization Assay with Tunable Dynamic Range Using Immobilized Quantum Dots As Donors in Fluorescence Resonance Energy Transfer

Abstract: A multiplexed solid-phase nucleic acid hybridization assay on a paper-based platform is presented using multicolor immobilized quantum dots (QDs) as donors in fluorescence resonance energy transfer (FRET). The surface of paper was modified with imidazole groups to immobilize two types of QD-probe oligonucleotide conjugates that were assembled in solution. Green-emitting QDs (gQDs) and red-emitting QDs (rQDs) served as donors with Cy3 and Alexa Fluor 647 (A647) acceptors. The gQD/Cy3 FRET pair served as an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 36 publications
2
75
0
Order By: Relevance
“…In addition, hybridization reactions done with uidA(93) FC TGT that was fortified with 86% (v/v) goat serum in BBS showed the same response as the hybridization reactions done in BBS only and retained excellent resistance to non-specific adsorption of oligonucleotides (see Figure S5 for details). These results are consistent with our previous studies that have also shown that the GSH-QDs exhibit excellent resistance to non-specific adsorption of oligonucleotides for the development of paper-based QD-FRET nucleic acid hybridization assays [34,35].…”
Section: Single Nucleotide Polymorphism Detectionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, hybridization reactions done with uidA(93) FC TGT that was fortified with 86% (v/v) goat serum in BBS showed the same response as the hybridization reactions done in BBS only and retained excellent resistance to non-specific adsorption of oligonucleotides (see Figure S5 for details). These results are consistent with our previous studies that have also shown that the GSH-QDs exhibit excellent resistance to non-specific adsorption of oligonucleotides for the development of paper-based QD-FRET nucleic acid hybridization assays [34,35].…”
Section: Single Nucleotide Polymorphism Detectionsupporting
confidence: 93%
“…For these experiments, the GSH-QDs were modified with SMN1 probes. The optimization of stringency conditions for SNP discrimination was based on our previously published results that involved a concurrent adjustment of the ionic strength and formamide concentration of the solution [34,35]. This method for SNP discrimination is advantageous as it allows mismatch discrimination at room temperature conditions.…”
Section: Single Nucleotide Polymorphism Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] QDs are popular RET donors due to their high quantum yield and tuneable photoluminescence (PL).The surface area of QDs allows the immobilization of multiple recognition elements, where a single QD can participate in multiple RET events [1]. Our group has paired green-emitting QDs (gQDs) and red-emitting QDs (rQDs) with various molecular dyes as RET acceptors in nucleic acid hybridization assays [2,3].While QDs are popular RET donors, their use as RET acceptors has been limited to time gated measurements [4], chemiluminescence resonance energy transfer (CRET) [5] and bioluminescence resonance energy transfer (BRET) [6]. The broad absorbance band of QDs that stretches into the UV region of the spectrum makes them susceptible to direct excitation in the process of exciting the RET donor.…”
Section: Quantum Dots In Resonance Energy Transfermentioning
confidence: 99%